Chromium (VI) remediation in aqueous solution by waste products (peel and seed) of mango (Mangifera indica L.) cultivars - Sampaio, Caroline de Goes; Owen, Robert (Environmental science and pollution research, 2019)
The surface group characteristics of mango cultivar peels and seeds were evaluated by infrared spectra, PZC, and functional group composition. The adsorption/reduction of chromium (VI) in aqueous solutions was investigated by varying pH, contact time, initial Cr(VI) concentration, and adsorbent amount. The results show that both peel and seed powders of the mango cultivars showed significant adsorption/reduction capacity for Cr(VI) and that the desorption process obeys pseudo-second-order kinetics. Optimal adsorption occurred at pH 1.0, using a Cr(VI) concentration of 100 mg/L. On average, at pH 1.0, and a concentration of 3 g/L, the maximum adsorption/reduction capacity of Cr(VI) was 83% (peels 76%, seeds 90%). Of the mango powders tested, the most efficient were Tommy seed (100%) and Coite peel (98%) followed by Coite seed (96%) and Tommy peel powders (95%). The adsorption/reduction of Cr(VI) was complete (100%) by the mango seed, in comparison to the peel powders (97%) after 180 min. The data indicates that mango waste products, such as seed and peel powders, are both excellent candidates for the remediation of Cr(VI) from aqueous systems and due to the higher concentration of gallates and galloyl glucosides, the mango seed powders should be the powders of choice for future remediation projects.
Gesehen am 16.05.2019